2019
DOI: 10.3389/fphys.2019.00228
|View full text |Cite
|
Sign up to set email alerts
|

Transient Inhibition of mTORC1 Signaling Ameliorates Irradiation-Induced Liver Damage

Abstract: Recurrent liver cancer after surgery is often treated with radiotherapy, which induces liver damage. It has been documented that activation of the TGF-β and NF-κB signaling pathways plays important roles in irradiation-induced liver pathologies. However, the significance of mTOR signaling remains undefined after irradiation exposure. In the present study, we investigated the effects of inhibiting mTORC1 signaling on irradiated livers. Male C57BL/6J mice were acutely exposed to 8.0 Gy of X-ray total body irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…In this experiment combination of RAPA with ACRL decreased significantly the hepatoxicity of ACRL indicated by a significant reduction in the expression of caspase‐3 and RIPK‐1 signifying a marked reduction in apoptosis and necroptosis pathways and promotion of the survival autophagic strategy through the inhibition of mTOR pathway (Figure 9). This cytoprotective effect of RAPA in liver injury had been shown by Yang et al (2019) when the hepatic apoptotic cells markedly decreased after treatment with RAPA. A similar enhancing role of rapamycin in the autophagic process and inhibition of cell apoptosis had been reported during renal ischemia (Li et al, 2018) and induced nephropathy (Liang et al, 2017).…”
Section: Discussionsupporting
confidence: 66%
“…In this experiment combination of RAPA with ACRL decreased significantly the hepatoxicity of ACRL indicated by a significant reduction in the expression of caspase‐3 and RIPK‐1 signifying a marked reduction in apoptosis and necroptosis pathways and promotion of the survival autophagic strategy through the inhibition of mTOR pathway (Figure 9). This cytoprotective effect of RAPA in liver injury had been shown by Yang et al (2019) when the hepatic apoptotic cells markedly decreased after treatment with RAPA. A similar enhancing role of rapamycin in the autophagic process and inhibition of cell apoptosis had been reported during renal ischemia (Li et al, 2018) and induced nephropathy (Liang et al, 2017).…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, Phe and Tyr stimulated hyperactivation of the mTORC1 pathway in L-02 cells, which was restored by COS treatment ( Figures 5 G–5I), in line with the influence of COS treatment on the mTORC1 pathway in vivo ( Figure S6 ). It reported that transient inhibition of mTORC1 signaling by rapamycin inhibit cellular apoptosis, further against irradiation-induced liver damage, 28 suggesting that the activation of mTORC1 pathway might promote the hepatocyte apoptosis. In summary, this further emphasized that hepatocytes could be damaged by Phe and Tyr, which was responsible for the exacerbation of hepatic fibrosis, but the damage was reversed by COS treatment via the mTORC1 pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is radiosensitive, particularly in young animals[ 33 ]. Liver cancer, with high mortality, is one of the most common solid tumors in the world[ 34 ]. Although surgical resection is the first choice of treatment for hepatocellular carcinoma, radiation therapy is an actively used and essential treatment modality for locally advanced hepatocellular carcinoma or tumors in the upper abdomen, right lower lung, distal section of the esophagus, or whole body[ 4 , 5 , 35 ].…”
Section: Discussionmentioning
confidence: 99%